Jawabanmu

Jawaban paling cerdas!
2014-04-04T22:40:28+07:00
2x+3y=11      (x3)
3x - 2y= -16    (x2)

6x+9y=33
6x-4y=-32   -
   13y=65
      y=65/13
      y=5
2x+3y=11
2x+3(5)=11
2x+15=11
2x     =11-15
2x     =-4
x       =-4/2
x      =-2
jadi,-3a+2b=-3x+2y
                =-3(-2)+2(-2)
                =6+ -4
                =2
1 5 1
2014-04-05T00:45:03+07:00
2x+3y=11      (x3)
3x - 2y= -16    (x2)

6x+9y=33
6x-4y=-32   -
   13y=65
      y=65/13
      y=5
2x+3y=11
2x+3(5)=11
2x+15=11
2x     =11-15
2x     =-4
x       =-4/2
x      =-2
jadi,-3a+2b=-3x+2y
                =-3(-2)+2(-2)
                =6+ -4
                =2